THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND WORK STRESS ON TURNOVER INTENTION WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Lusiana Dwi Wahyuni; Sri Handari; Arni Surwanti (International Journal Labs, 2022)
This study aims to determine how transformational leadership and work stress influence turnover intention with job satisfaction as an intervening variable in contract employees in the Special Region of Yogyakarta. The respondents in this study were employees at the Yogyakarta Village Government Center, Cokroaminoto University Yogyakarta, and PT X Yogyakarta. The sample used was 125 respondents collected through the purposive convenience sampling technique. The research design used a quantitative approach and the Structural Equation Modeling (SEM) method as a data analysis technique. The results of this study show that transformational leadership did not significantly affect job satisfaction; work stress had a negative and significant effect on job satisfaction. The study's results also show that transformational leadership had a negative and significant effect on turnover intention, work stress does not affect turnover intention, and job satisfaction has a negative and significant effect on turnover intention. Another finding in this study is that transformational leadership did not affect turnover intention through job satisfaction as an intervening variable. The influence of transformational leadership on turnover intention was direct. Work stress affects turnover intention through job satisfaction as an intervening variable.